Long‐term outcomes of the Stop Traumatic OASI Morbidity Project (STOMP). Issue 3 (5th July 2018) - Basu, Maya; Smith, Dot
Abstract: Objective: To evaluate long‐term sustainability of the Stop Traumatic OASI Morbidity Project (STOMP) in reducing the incidence of obstetric anal sphincter injury (OASI). Methods: A prospective observational study of women undergoing vaginal delivery at a UK district general hospital between September 1, 2014, and February 28, 2017. The principles of STOMP involve encouraging upright positioning, verbal coaching to avoid expulsive pushing and to slow down delivery, and tactile support to the vertex to judge speed and slow down delivery. After a training period, STOMP was implemented for all vaginal deliveries. Clinical and demographic data on women affected by OASI were collected across a 30‐month period. The primary outcome measure was the incidence of OASI. Results: There were 8782 vaginal deliveries during the 30‐month period after implementation of STOMP. There was a significant decrease in the mean incidence of OASI relative to the 9 months before implementation ( P <0.001). There was a significant decrease in the incidence of OASI for both spontaneous vaginal and instrumental deliveries (both P <0.05). There was no change in the frequency of episiotomy. Conclusions: Implementation of STOMP led to a significant decrease in OASI, confirming the sustainability of this approach to improve outcomes. Abstract : Use of the STOMP bundle was associated with a significant and sustained decrease in obstetric anal sphincter injuries for both spontaneous and instrumental deliveries.